An Empirical Analysis of The Effect of Monetary Policy on Inflation in Nigeria; 1970 – 2018 - Darma, Nazifi Abdullahi; Abdulsalami, Ozovehe (Advances in Social Sciences Research Journal, 2020)
This study empirically analysed the effect of monetary policy on inflation in Nigeria; 1970 – 2018. The objective is to determine the effectiveness of monetary policy instruments on inflation in Nigeria. In doing this, relevant literature was reviewed and theoretical relationship between monetary policy and inflation was established following the quantity theory of money by Irving Fisher. The study employed time series data sourced from the statistical bulletin of Central bank of Nigeria (CBN) 2018. Stationarity test was also conducted on the time series data to determine the order of integration using Augmented Dickey Fuller (ADF) test. The unit root test revealed that inflation rate was stationary at level i.e. I(0) while monetary policy rate, treasury bill rate and cash reserve ratio were stationary at first difference i.e. I(1). The estimated results showed that there is cointegration between monetary policy variables and inflation rate in Nigeria. The results revealed that Monetary Policy Rate (MPR) was statistically significant in the short run after first difference, which indicates that monetary policy rate (MPR) exerts significant effect on inflation in Nigeria in the short run. Based on these findings, the study concluded that monetary policy variables alone are not sufficient enough in maintaining price stability in Nigeria. Therefore, the Federal government, Central Bank of Nigeria (CBN) and policy makers should simultaneously use monetary and fiscal policy instruments to maintain price stability in Nigeria.